2009
DOI: 10.1037/a0015058
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to attentional impairments after traumatic brain injury.

Abstract: The aim of the present study was to investigate the contribution of impaired information processing speed and strategic control of attention to performance on attentional tasks after traumatic brain injury (TBI). Forty moderately to severely injured rehabilitation inpatients and 40 healthy controls completed a selection of attentional tasks. Slowed processing speed in the TBI group was identified on the Symbol Digit Modalities Test (SDMT), 2&7 Selective Attention Test (2&7), Selective Attention (SAT), and Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 52 publications
6
41
1
Order By: Relevance
“…It is therefore not surprising that poorer connectivity both globally in the brain and locally in large numbers of regional cortical areas could result in slower processing speed. The globally distributed nature of processing speed performance observed here is consistent with observations that brain lesions associated with variable etiologies and locations may commonly produce impairments in processing speed (DeLuca et al, 2004;Habekost and Rostrup, 2007;Willmott et al, 2009). Such a global network may be expected to be more vulnerable to disruptions due to age-related neuropathological changes in any part of the network resulting in a loss of efficiency and leading to a decline in processing speed that is typically associated with aging (Salthouse, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…It is therefore not surprising that poorer connectivity both globally in the brain and locally in large numbers of regional cortical areas could result in slower processing speed. The globally distributed nature of processing speed performance observed here is consistent with observations that brain lesions associated with variable etiologies and locations may commonly produce impairments in processing speed (DeLuca et al, 2004;Habekost and Rostrup, 2007;Willmott et al, 2009). Such a global network may be expected to be more vulnerable to disruptions due to age-related neuropathological changes in any part of the network resulting in a loss of efficiency and leading to a decline in processing speed that is typically associated with aging (Salthouse, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Deficits in working memory are common following TBI in children (20,21) and adolescents (41,47) and are presumed to be related to underlying pathology or dysfunction in the neuron networks. Previous studies have demonstrated that in the long-term phase after TBI, there are significant parenchymal differences, including smaller frontal and cingulate white and gray matter volumes (23,45,48), reduced cortical thickness in the frontal lobes (31), pronounced cortical abnormalities on surface-based morphometry in the frontal lobes (40), and histologic evidence of reduced cortical thickness associated with neuronal loss in the cortical mantle following TBI in the frontal and cingulate regions (30).…”
Section: Introductionmentioning
confidence: 98%
“…Reduced information processing speed is extremely common post injury, along with impairments in attention, working memory, and executive function (Willmott, Ponsford, Hocking, & Schönberger, 2009). These cognitive impairments interfere with an individual's ability to undertake everyday activities due to difficulty keeping pace with time pressures, juggling several tasks or pieces of information simultaneously, and managing complex interpersonal interactions (Ponsford & Willmott, 2004).…”
mentioning
confidence: 99%